Editors' Introduction - Edouard Machery; Jesse Prinz (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
The relation between concepts and perception has been a central issue in the philosophy of mind and cognitive science for a few decades, and it has recently been rejuvenated by research on concept empiricism and on cognitive penetration. Research on the relation between concepts and perception in philosophy and in the cognitive sciences focuses on several distinct issues.